A Mixed‐Methods Study of Nurse Managers' Managerial and Clinical Challenges in Mental Health Centers During the COVID‐19 Pandemic. Issue 6 (15th June 2021) - Kagan, Ilya; Shor, Razya; Ben Aharon, Iris; Yerushalmi, Sarit; Kigli‐Shemesh, Ronit; Gelman, Sophi; Itzhaki, Michal
Abstract: Purpose: The worldwide outbreak of the COVID‐19 pandemic has posed challenges for nurses. The aim of this study was to examine the managerial and clinical challenges of nurse managers in mental health centers during the current COVID‐19 pandemic. Design: A mixed‐methods study based on an analysis of data obtained in focus groups with 25 nurse managers from two mental health centers in Israel. Methods: The quantitative phase was conducted prior to the group sessions using a structured self‐administered questionnaire that examined the nurse managers' (a) background data, (b) communication with the staff nurses, (c) perceptions of nurses' functioning, (d) perceptions of their own functioning, and (e) management as impacted by the pandemic. The qualitative phase included three sessions of focus groups in which the nurse managers discussed both their challenging and positive issues during the pandemic. Findings: The most important challenges were related to the need to protect patients from infection and communicating with families and primary caregivers. Work policies and procedures were less well adapted to pandemic conditions; nevertheless, nurse managers felt a sense of purpose, duty, and pride in their work. Three themes emerged: (a) "management complexity" included the change from a familiar routine to a new reality, working in capsules, protecting against infection, functional confusion, and insights into future epidemics; (b) "challenging communication" included communication with patients through glass walls and communication with staff through screens and (c) "bright spots" referred to staff cohesion and the provision of respectful care. Conclusions: Mental health nurse managers have experienced during the pandemic a change in their roles from being less managerial to focusing more on clinical work. Communication between nurse managers and staff nurses and between mental health patients and staff were the main challenges. Nurse managers favorably noted the uniformity and humanity of the staff, sense of cohesion, and shared responsibility. Clinical Relevance: In the first wave of the pandemic, there was confusion as to the functional role of ward nurse managers, as the focus of their activities became more clinical and less managerial. During and after the pandemic, preventive interventions should be carried out in order to assist patients, staff nurses, and nurse managers in mental health centers.